The Crowding Out Effect of Public Investment revisited: A Comparative SVAR Analysis of Sweden and the United States - Huzell,Oscar; Nordén,Simon (2023)
Our study investigates the crowding out effect of public investment on private investment in Sweden and the United States during the period 2005-2019. We present an account of the prevailing theory on the subject and let it inform our subsequent SVAR analysis on quarterly data. We obtain impulse response functions to assess the direction and extent of crowding out or crowding in effects for both countries. Further, we consult the Granger causality test and forecast error variance decomposition analysis to expand our results. Our results indicate that neither effect is prevalent in Sweden and we find evidence for a Crowding out effect in the United States.
Keywords: Public investment; Private investment; Crowding-out; SVAR